Effect of brazing current on microstructure and mechanical behavior of WC-Co/AISI 1020 steel TIG brazed joint. (April 2017) - Cheniti, B.; Miroud, D.; Badji, R.; Allou, D.; Csanádi, T.; Fides, M.; Hvizdoš, P.
Abstract: In this work, the WC-Co carbide/1020 steel brazed joints which were prepared by Tungsten Inert Gas (TIG) process using different brazing currents have been studied. The peak temperature reached by increasing the brazing current caused remarkable inter-diffusion of Ni, Mn, Cu and Co elements between the braze and the base materials. The higher the brazing current was, the larger the diffusion extent of these elements became and the greater the WC rearrangement occured. As the diffusion rate of Ni towards the WC-Co was enhanced through increasing brazing current, a short range diffusion of Co element towards the braze was recorded. A Special Shear Test (SST) conducted at room temperature revealed the best bonding strength for the current of 80A. Besides, hardness (HIT ) and elastic modulus (EIT ) values of the interfaces were situated between those of the braze and the base materials. Highlights: WC-Co cermet has been brazed to 1020 steel using Ag based filler alloy by the Tungsten Inert Gas process. The brazed joints are characterized by the thermally affected region devoid in Cobalt element. The increase of the current density caused a WC rearrangement along the braze/WC-Co cermet interface. The mechanical properties of the brazed joint have been improved by increasing the brazing current.